Risk Management in Information Technology Project: An Empirical Study - Kornelius Irfandhi (ComTech: Computer, Mathematics and Engineering Applications, 2016)
The companies are facing some risks due to changes in a dynamic environment. If risks are not managed properly, it will have some negative impacts on the companies at the present and the future. One important function of the Information Technology (IT) governance is risk management. Risk management in IT project aims to provide a safe environment for IT projects undertaken. Risk management becomes an important process for the success of IT projects. This article discussed the risk of IT project and whether there was a relationship between risk management and the success of the project. The method used was performing a literature review of several scientific articles which published between 2010 and 2014. The results of this study are the presence of risk management and risk manager influence the success of the project. Risk analysis and risk monitoring and control also have a relationship with the subjective performance of IT projects. If risk management is applied properly, the chance of the success of the projects undertaken can be increased.